Hypoalbuminemia is an Independent Predictor of 30-Day Postoperative Complications Following Surgical Fixation of Ankle Fractures. Issue 4 (22nd October 2020) - Kukowski, Nathan; Wilson, Jacob M.; Bariteau, Jason T.; Staley, Christopher A.
Category: Basic Sciences/Biologics; Trauma; Other Introduction/Purpose: Malnutrition is known to be negatively associated with outcomes after multiple orthopedic procedures. We hypothesized that admission albumin levels, as a maker for malnutrition, would correlate with postoperative outcomes. The purpose of this study is to investigate this relationship following surgery for ankle fracture. Methods: This is a retrospective cohort study of the ACS-NSQIP database. Patients undergoing operative fixation of an ankle fracture were identified. 6, 138 patients with albumin available for analysis were identified. Baseline patient information, preoperative serum albumin levels, 30-day postoperative complications, readmission, reoperation, and length of stay data were then collected. Poisson regression with robust error variance was performed to assess the effect of preoperative serum albumin level on postoperative outcomes. Results: 6, 138 patients with albumin available for analysis were identified in the database. The mean albumin level was 3.86 g/dl and 20.3% of patients with available albumin levels were hypoalbuminemic. Multivariate analysis revealed that albumin level <3.5 g/dl is an independent risk factor for complication (RR 1.42, 95% CI 1.13-1.78, p=0.002) and readmission (RR 1.54, 95% CI 1.13- 2.08, p =0.006). Additionally, when analyzed as a continuous variable, albumin level was negatively correlated with risk of mortality (RR 0.37, 95% CI 0.19-0.72, p=0.003). Patients with hypoalbuminemia also had significantly longer length of stays (4.5 v. 2.1 days, p<0.001). Conclusion: While complication rates after fixation of ankle fractures remain low, hypoalbuminemia is a predictor of postoperative course. Malnutrition, therefore, may help inform the decision between surgical and conservative management of patients with ankle fractures potentially amenable to non-operative management. Additionally, hypoalbuminemia should trigger heightened awareness and prophylactic therapy where appropriate.